2021
DOI: 10.3390/ani11061502
|View full text |Cite
|
Sign up to set email alerts
|

Morphometrical Study of the Lumbar Segment of the Internal Vertebral Venous Plexus in Dogs: A Contrast CT-Based Study

Abstract: The internal vertebral venous plexus (IVVP) is a thin-walled, valveless venous network that is located inside the vertebral canal, communicating with the cerebral venous sinuses. The objective of this study was to perform a morphometric analysis of the IVVP, dural sac, epidural space and vertebral canal between the L1 and L7 vertebrae with contrast-enhanced computed tomography (CT). Six clinically healthy adult dogs weighing between 12 kg to 28 kg were used in the study. The CT venographic protocol consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In humans, the epidural venous plexus is most prominent in the thoracic spine, and spontaneous spinal epidural hematomas most often occur in the thoracic and cervicothoracic region, followed by the thoracolumbar area 5,6,14,15 . In dogs, the venous plexus has been evaluated morphometrically in the cervical and lumbar spine 16‐18 . In a study evaluating the lumbar intervertebral venous plexus, the venous plexus was found to occupy the highest percentage of area relative to the vertebral canal most cranially at L1 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, the epidural venous plexus is most prominent in the thoracic spine, and spontaneous spinal epidural hematomas most often occur in the thoracic and cervicothoracic region, followed by the thoracolumbar area 5,6,14,15 . In dogs, the venous plexus has been evaluated morphometrically in the cervical and lumbar spine 16‐18 . In a study evaluating the lumbar intervertebral venous plexus, the venous plexus was found to occupy the highest percentage of area relative to the vertebral canal most cranially at L1 18 .…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 , 14 , 15 In dogs, the venous plexus has been evaluated morphometrically in the cervical and lumbar spine. 16 , 17 , 18 In a study evaluating the lumbar intervertebral venous plexus, the venous plexus was found to occupy the highest percentage of area relative to the vertebral canal most cranially at L1. 18 Given these findings, the potential for EH should be considered more highly in French Bulldogs with neurologic exam abnormalities localizing more cranially.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, until recently, studies on the CT anatomy of venous drainage of the vertebral column and associated structures in dogs did not specifically visualize the basivertebral veins 30,31 . A recent publication did just so, although this study did not specifically report on the osseous canal or foramina in the vertebral body that allow passage of this often paired vein 32 . What characterizes a vascular canal of the vertebral body as “normal” (i.e., what dimensions or shapes are deemed “normal”) is not reported in veterinary literature.…”
Section: Discussionmentioning
confidence: 92%
“…30,31 A recent publication did just so, although this study did not specifically report on the osseous canal or foramina in the vertebral body that allow passage of this often paired vein. 32 What characterizes a vascular canal of the vertebral body as "normal" (i.e., what dimensions or shapes are deemed "normal") is not reported in veterinary literature. In human literature, several characteristics of basivertebral foramina and the basivertebral canal are published.…”
Section: Discussionmentioning
confidence: 99%
“…The other species of domestic mammals studied in three of the articles were the dog and the cat. The research article by Ariete et al [ 5 ], which referred to the canine internal vertebral venous plexus (IVVP) of the lumbar segment, used contrast-enhanced computed-tomography (CT) to conduct a morphometrical study of the aforementioned vessels, the dural sac, and the vertebral canal. As part of the vertebral venous plexus, this IVVP is made of a paired thin-walled and valveless venous vessels with a rhomboidal pattern, placed on the floor of the vertebral canal, and included in the lumbar epidural space.…”
mentioning
confidence: 99%